Environmental regulation and productivity growth in the euro area: Testing the Porter hypothesis - Nicola Benatti; Martin Groiss; Petra Kelly; Paloma López-García (European Central Bank (ECB), 2023)
This paper analyses the impact of changes in environmental regulations on productivity growth at country- and firm-level. We exploit several data sources and the environmental policy stringency index, to evaluate the Porter hypothesis, according to which firms' productivity can benefit from more stringent environmental policies. By using panel local projections, we estimate the regulatory impact over a five-year horizon. The identification of causal impacts of regulatory changes is achieved by the estimation of firms' CO2 emissions via a machine learning algorithm. At country- and firm-level, policy tightening affects high-polluters' productivity negatively and stronger than their less-polluting peers. However, among high-polluting firms, large ones experience positive total factor productivity growth due to easier access to finance and greater innovativeness. Hence, we do not find support for the Porter hypothesis in general. However for technology support policies and firms with the required resources, policy tightening can enhance productivity.
Keywords: O44; Q52; Q58; 330; Environmental regulation; Emissions; Porter hypothesis; Productivity; Euro Area